Sistem Informasi Penjualan Berbasis Kinerja pada Proyek Apartemen Mega City Bekasi - Dyani Ayu Aisyah; Kursehi Falgenti (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2017)
Mega City Apartment Bekasi is an integrated residence with shopping and office center developed by PT. Mega Utama Development. The sales data encountered in the Mega City apartment project is still manualy by using speadsheet application. There has been no centralized data processing with an application support, especially marketing division. The purpose of this study to build a performance-based sales information system at PT. Mega Utama Development. The method used in developing this information system is SDLC. The SDLC model used in the development of this information system is the